Optimal Level of Assistance and Weight of Hip-joint Wearable Robot Considering Influences to the Human Body. Issue 22 (2019) - Kim, Yoosuk; Shin, Sungwon; Kong, Kyoungchul; Han, Dyhyun
Abstract: There have been many studies on design and control of hip-joint wearable robots, a part of which have already been commercialized. However, the clear assistance effects of the wearable robot on the human body have not been studied much yet. Although the human body dynamics may be considered in the robot design stage, it is difficult to predict the resultant after wearing the robot due to the complicated nature of human-robot interaction. Another difficulty in designing a hip-joint wearable robot is that the weight of the robot must be taken into consideration because the wearer must fully bear the whole weight of the robot. If a high performance actuator is used to provide greater assistance, the weight of the robot will inevitably increase, putting a burden on the human body. In this paper, musculoskeletal simulation is utilized to predict and analyze the effects of assistance and weight of robot on the human body. Then, the reliability of the simulation is verified through the wearable robot experiment. Furthermore, the relationship between assistance and weight of the robot is derived from the specifications of the commercial hip-joint wearable robots. As a result of the parameter study by applying this relationship, the optimal hip-joint wearable robot weight that the human can receive the best assistance effect is obtained.